2023
DOI: 10.3390/plants12173116
|View full text |Cite
|
Sign up to set email alerts
|

Autotetraploid Origin of Chinese Cherry Revealed by Chromosomal Karyotype and In Situ Hybridization of Seedling Progenies

Yan Wang,
Xueou Li,
Yan Feng
et al.

Abstract: Polyploidy is considered a driving force in plant evolution and diversification. Chinese cherry [Cerasus pseudocerasus (Lindl.) G.Don], an economically important fruit crop native to China, has evolved at the tetraploid level, with a few pentaploid and hexaploid populations. However, its auto- or allo-polyploid origin remains unclear. To address this issue, we analyzed the ploidy levels and rDNA chromosomal distribution in self- and open-pollinated seedling progenies of tetraploid and hexaploid Chinese cherry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Our investigation revealed that, similar to other species within the Rosaceae, P. conradinae underwent a common WGD event. As it is a tetraploid species (Wang et al 2023 ), we propose that, in addition to this WGD event shared with other members of the Rosaceae family, P. conradinae has experienced a lineage-specific polyploidy event. However, predicting this event based solely on homologous genes remains challenging.…”
Section: Discussionmentioning
confidence: 83%
“…Our investigation revealed that, similar to other species within the Rosaceae, P. conradinae underwent a common WGD event. As it is a tetraploid species (Wang et al 2023 ), we propose that, in addition to this WGD event shared with other members of the Rosaceae family, P. conradinae has experienced a lineage-specific polyploidy event. However, predicting this event based solely on homologous genes remains challenging.…”
Section: Discussionmentioning
confidence: 83%
“…Fruit samples of SGF (10 days after full bloom [DAFB]), VF (25 DAFB), and RF (40 DAFB) stages from ‘Heizhenzhu’ were collected at the cherry orchard of Shanghai Yingzhiyuan Agricultural Technology Co., Ltd (121°32′56″ N, 30°56′45″ E). The detailed analysis procedures followed published descriptions [ 9 ]. In addition, six Chinese cherry varieties (‘Zhuji Duanbing’, ‘Xiangxing’, ‘Manaohong’, ‘Zhushahong’, ‘Lixianxiaoyingtao’, and ‘Wenchuanxiaoheiyingtao’) and three sweet cherry varieties (‘Lita’, ‘Daxing’, and ‘Geleisixing’) were collected at the orchard of the Sichuan Academy of Agricultural Sciences (30°46′47″ N, 104°12′30″ E).…”
Section: Methodsmentioning
confidence: 99%
“…Although Darwin's theory and the Modern Synthesis emphasized natural selection, they did not clarify why and how organisms can exist. Additionally, they posited that natural selection, genetic drift, competition, or mutations are the driving forces of evolution [63][64][65][66][67], but these factors require energy and do not provide energy for the evolution of CBMs. This is analogous to the fact that an engine is essential for a fuel-powered car to run, but the engine itself cannot provide the driving force for the car.…”
Section: Novelties Of the Cbetmentioning
confidence: 99%